Case Study on Energy Consumption and Electrical Systems in the Provincial Government Building of ABC - Luqvi Rizki Syahputra; Todo Hotma Tua Simarmata; Hendry Guntur Kusumanegara; Nico Juni Ferson (International Journal Labs, 2025)
The increasing demand for electrical energy is driven by the growth in office activities, particularly in government buildings that operate nearly all day. The ABC Provincial Government Building, as a hub for administration and public services, experiences high electricity consumption, leading to energy waste, higher operational costs, and environmental impacts through carbon emissions. Additionally, the electrical systems in such buildings are often not periodically assessed for efficiency, reliability, and compliance with energy conservation standards. This research aims to analyze energy consumption levels in the ABC Provincial Government Building using a qualitative descriptive research method with a case study approach. Data collection was conducted through literature reviews, document studies, and observations. The data were analyzed in three stages: data reduction, data presentation, and conclusion drawing. Results from an energy audit at the ABC Building, with 6,600 VA of installed electrical power, show an Energy Consumption Intensity (IKE) of 50 kWh/m²/year by 2024. Although energy consumption is measurable, energy management and conservation policies have not been fully optimized. Significant energy savings are possible through better management of air conditioning, lighting, and office equipment, along with the installation of a 50 kWp rooftop solar power system. If all recommendations are implemented, energy consumption could be reduced by up to 77%, leading to considerable energy cost savings and a notable reduction in carbon emissions.